Intervenciones de enfermería y su incidencia en los cuidados postmortem del área de medicina interna del Hospital General Alfredo Noboa Montenegro, Guaranda – Bolívar, periodo mayo – septiembre del 2019. - Allauca Miranda, Joselyn Natalia (2019)
Nursing interventions in post-mortem care are essential and are governed by the corresponding protocols, which must be applied after confirmation of clinical death by the responsible physician, for immediate communication to family members, who frequent it and who They start the aforementioned process. In the development of the present investigative work it is tried to show the incidence of the nursing interventions in the post-mortem care of the internal medicine area of the General Alfredo Noboa Montenegro Hospital, for which the deductive, inductive and synthesis analysis methods were also applied with a mixed modality being qualitative and quantitative, the types of non-experimental, descriptive and field research, applying as observation techniques the observation sheet, the nursing staff survey of the area in question. Obtaining as results that the interventions of the nurses have not been completely acceptable and greater effectiveness is required in the application of the protocols, especially regarding family care and the social impact on it and for society, which It generates certain inconveniences and discomforts that must be addressed to improve its operation of the area, for which the following theoretical proposal is formulated, which consists in developing an awareness program, on post-mortem care and the reduction of social impact.